Seberapa Besar Kepemilikan Saham Berperan Dalam Penentuan Nilai Perusahaan Dengan Tinjauan Agency Theory - Yuniningsih, Yuniningsih (IAI Darussalam, 2017)
This study is about how the ownership of the company's financial, the management company and the conflict of interest arises. Shareholding in this article is managerial ownership and institutional ownership. This study aims to test and analyze how much the ownership of companies, both managerial and institutional in determining the value of companies with an overview of the Agency Theory. Mechanical analysis using multiple linear regression analysis. Population 37 companies, using purposive sampling the sample contained 8 specialized manufacturing company Consumer Goods Industry Sector listed on the Stock Exchange from 2012 - 2015. The results show Managerial ownership did not show a significant role in determining the value of the Company. Moderate Institutional ownership has a significant role in determining the value of the company